Banisteriopsis Species: A Source of Bioactive of Potential Medical Application - Frias, Ulysses A. de; Mendes Costa, Maria Cristina; Takahashi, Jacqueline Aparecida; Oki, Yumi (International Journal of Biotechnology for Wellness Industries, 2012)
In recent years, interest in further development of herbal or botanical drug products derived from traditional preparations has been increasing steadily. Plants have been used for thousands of years to treat health disorders and to prevent diseases including epidemics. Several research works have been developed to search for new natural products to be used in pharmaceutical products. Active compounds produced during secondary metabolism are responsible for the biological properties of the plant species and may be used to most diverse purposes, including treatment of several diseases. Banisteriopsis species has been described showing interesting activities by its use in popular medicine. The mainly use was described to production of the Ayahuasca, an Amazonian psychotropic plant tea obtained from Banisteriopsis caapi, which contains β-carboline alkaloids, mainly harmine, harmaline and tetrahydroharmine. Other species of Banisteriopsis genus have been described with biological metabolites as antimicrobial, anticholinesterase, antianxiety and others. These biological activities were described chiefly by the presence of alkaloids, flavonoids, tannins. Thus, to stimulate the study into the Banisteriopsis genus, the purpose of the present review is to gather information on the use of the extracts and metabolites of Banisteriopsis species (Malpighiaceae) as a resource to diseases treatment or to pharmaceutical purposes.